The interplay between the material and non-material pneumatology in Pentecostalism: a pneumatological Pentecostal theology of materiality - Mookgo Solomon Kgatle (Pharos Journal of Theology, 2025)
Pneumatology also known as the theology of the Spirit within the Pentecostal movement is one of its fundamental teachings. This theology has been studied from both the non-material and material perspectives. This article looks at the possibility of bringing both the non-material and the material pneumatology through Pneumatological imagination. Pneumatological imagination in the works of Amos Yong and the Pentecost narrative in Lukan-Acts demonstrates that the coming of the Spirit has both material and non-material significance. The Holy Spirit although coming from the Father (divine) dwelt among the humane resulting in tangible works such as tongues of fire, mighty wind, and language of nations (xenolalia). Therefore, a pneumatological imagination is relevant for bringing together material and non material pneumatology in an integrative way. This understanding is important for the development of the Pentecostal pneumatological theology of materiality. Such a Theology must be grounded in the indwelling of the non-material Holy Spirit. But at the same time be able to result in the material pneumatic experiences in the life of the believer. This theology engages the creation including fellow human beings. The aim is to demonstrate the relevance of this theology in the understanding of material Pentecostalism.